2023
DOI: 10.1021/acs.iecr.3c01588
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catalytic Oxidation of Ethylbenzene to Acetophenone: A Review of Catalyst Systems and Reaction Mechanisms

Musa O. Azeez,
Sodiq Adeyeye Nafiu,
Taofiq Abdulraheem Olarewaju
et al.

Abstract: Acetophenone is an important chemical intermediate often employed in the production chain of many pharmaceuticals, agrochemicals, food, and cosmetic products. It is industrially produced as a byproduct of the Hock process. However, a growing demand for acetophenone has necessitated consideration of alternative production routes. The oxidation of ethylbenzene to acetophenone (OEB-A) is one of the most considered alternatives due to the low cost and availability of ethylbenzene (EB). The EB is one of the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 254 publications
0
5
0
Order By: Relevance
“…4−6 Previous explorations have shown that homogeneous catalytic systems where catalysts can be fully dissolved in the reaction media can generally obtain good reaction results in the oxidation of EB to yield AP under mild reaction conditions, due to the enhanced interaction between catalytically active sites and substrates. 4,7,8 Despite these advantages, the features of easy separation and good recyclability strongly push scientists and engineers to put more emphasis on heterogeneous catalytic processes, which are more challenging to study and hence optimize compared with homogeneous ones. To this end, a wide range of solid catalysts have been explored for the selective oxidation of EB using different kinds of oxidants and solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4−6 Previous explorations have shown that homogeneous catalytic systems where catalysts can be fully dissolved in the reaction media can generally obtain good reaction results in the oxidation of EB to yield AP under mild reaction conditions, due to the enhanced interaction between catalytically active sites and substrates. 4,7,8 Despite these advantages, the features of easy separation and good recyclability strongly push scientists and engineers to put more emphasis on heterogeneous catalytic processes, which are more challenging to study and hence optimize compared with homogeneous ones. To this end, a wide range of solid catalysts have been explored for the selective oxidation of EB using different kinds of oxidants and solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The selective oxidation of alkanes represents a crucial route for introducing oxygen-containing functional groups. Typically, AP, obtained from the oxidation process of benzylic C–H of EB, serves as a popular chemical intermediate for the synthesis of value-added chemicals, such as resins, soaps, perfumes, flavorings, and plasticizers. Previous explorations have shown that homogeneous catalytic systems where catalysts can be fully dissolved in the reaction media can generally obtain good reaction results in the oxidation of EB to yield AP under mild reaction conditions, due to the enhanced interaction between catalytically active sites and substrates. ,, Despite these advantages, the features of easy separation and good recyclability strongly push scientists and engineers to put more emphasis on heterogeneous catalytic processes, which are more challenging to study and hence optimize compared with homogeneous ones. To this end, a wide range of solid catalysts have been explored for the selective oxidation of EB using different kinds of oxidants and solvents. Among them, some catalysts exhibited either good activity or AP selectivity, but the attainment of both high activity and selectivity in a sole catalyst is rather limited, especially with only oxygen as the oxidant and without the use of solvents.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, heterogeneous catalysis is regarded as a green and sustainable synthetic method, which makes it a preferred option for EB oxidation. Due to variable oxidation states, many transition metals have been widely employed in catalyzed EB conversion . Among transition metals, cobalt­(II) is the one that has been extensively studied. , The catalytic activity can also be significantly improved through the synergistic interaction between different transition metal active centers .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Researchers have ingeniously coated the surface of these magnetic nanoparticles with diverse molecules, unlocking their potential in effective catalytic processes and driving significant advancements in chemical research. 17,18 The increasing focus on green chemistry aims to replace costly, hazardous, and polluting catalysts with environmentally friendly and highly stable heterogeneous catalysts. 19…”
Section: Introductionmentioning
confidence: 99%